2021
DOI: 10.1001/jamacardio.2021.2321
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronary Artery Calcium Scoring to Guide Statin Therapy Allocation According to Risk-Enhancing Factors

Abstract: Guideline on the Management of Blood Cholesterol recommends the use of risk-enhancing factor assessment and the selective use of coronary artery calcium (CAC) scoring to guide the allocation of statin therapy among individuals with an intermediate risk of atherosclerotic cardiovascular disease (ASCVD). OBJECTIVE To examine the association between risk-enhancing factors and incident ASCVD by CAC burden among those at intermediate risk of ASCVD. DESIGN, SETTING, AND PARTICIPANTS The Multi-Ethnic Study of Atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 41 publications
4
40
0
1
Order By: Relevance
“…12 Indeed, it has been recently suggested that coronary calcium can enhance the classification of individuals at intermediate risk of atherosclerotic CVD. 13 Therefore, a multiterritorial vascular assessment, which is being adopted by epidemiological studies on subclinical atherosclerosis, 11 provides a richer information compared with single territories assesment. 14 Using data of the AWHS (Aragon Workers Health Study), our study investigated, for the first time, the association of a panel of toxic metals (sum of inorganic arsenic, barium, cadmium, chromium, antimony, titanium, uranium, vanadium, and tungsten) as measured in urine, with a comprehensive panel of subclinical atherosclerosis measures, including atherosclerosis presence at the carotid, femoral, and coronary territories.…”
mentioning
confidence: 99%
“…12 Indeed, it has been recently suggested that coronary calcium can enhance the classification of individuals at intermediate risk of atherosclerotic CVD. 13 Therefore, a multiterritorial vascular assessment, which is being adopted by epidemiological studies on subclinical atherosclerosis, 11 provides a richer information compared with single territories assesment. 14 Using data of the AWHS (Aragon Workers Health Study), our study investigated, for the first time, the association of a panel of toxic metals (sum of inorganic arsenic, barium, cadmium, chromium, antimony, titanium, uranium, vanadium, and tungsten) as measured in urine, with a comprehensive panel of subclinical atherosclerosis measures, including atherosclerosis presence at the carotid, femoral, and coronary territories.…”
mentioning
confidence: 99%
“…Nevertheless, it must also be noted that 30% of them had CAC = 0. Although data on incident events are still not available in MASALA, prior analyses of Multi-Ethnic Study of Atherosclerosis (MESA) participants at intermediate risk and with up to three risk enhancing features reported low ASCVD event rates if CAC = 0 [13,14]. Moreover, analyses in MESA and other cohorts with low baseline statin use have reported low 10-year event rates also among individuals with CAC = 0 and prediabetes/metabolic syndrome, which are frequent risk factors in non-diabetic SAs [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…First, as described above, the current lack of incident ASCVD data in MASALA mandates caution when extrapolating the protective prognosis associated with CAC = 0 to SA populations. Nonetheless, the favorable prognosis associated with CAC = 0 in MESA participants with other risk enhancing factors is reassuring [13,14]. Moreover, the favorable prognosis of CAC = 0 has also been confirmed in multiple other populations, including those considered at increased ASCVD risk [38].…”
Section: Study Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In these cases, the use of CACS may improve the allocation of newer therapies and identify patients at higher risk who will have greater benefit in risk reduction. However, although diabetic patients with zero calcium have good long-term prognosis, and recent findings suggest that among individuals at intermediate risk with risk-enhancing factors, cardiovascular event rates are generally lower than the recommended threshold to initiate statin therapy when the CACS is zero [ 25 ], statins should be given to diabetic patients according to current clinical guidelines until prospective studies are performed. The presence and severity of CACS was repeatedly shown to improve discrimination and reclassification of future cardiovascular risk when compared to traditional risk factors, including in patients with type 2 diabetes [ 20 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%